2015
DOI: 10.1515/biol-2015-0050
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of red alga Asparagopsis taxiformis extracts against Leishmania infantum

Abstract: Leishmaniasis is a disease with a worldwide distribution affecting both humans and animals. There is a need to identify and develop new drugs for the treatment of leishmaniasis. This study showed that crude ethanolic extracts of the red alga

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Researchers demonstrated that a concentration of 1 mg/mL of A. armata dichloromethane extracts was able to significantly reduce Human colorectal cancer model (Caco‑2 cells) proliferation, proving antitumoral bioactivity [ 218 ]. For another perspective, A. taxiformis extracts at a concentration of 40 µg/mL exhibited activity against the protozoan Leishmania infantum , which affects animals and humans [ 219 ]. Therefore, this red seaweed extract also demonstrated to be efficient in the inhibition of fungal growth, namely, Aspergillus fumigatus , Aspergillus terreus, and Aspergillus flavus [ 220 ].…”
Section: Pharmacological Potential Of the Invasive Seaweedsmentioning
confidence: 99%
“…Researchers demonstrated that a concentration of 1 mg/mL of A. armata dichloromethane extracts was able to significantly reduce Human colorectal cancer model (Caco‑2 cells) proliferation, proving antitumoral bioactivity [ 218 ]. For another perspective, A. taxiformis extracts at a concentration of 40 µg/mL exhibited activity against the protozoan Leishmania infantum , which affects animals and humans [ 219 ]. Therefore, this red seaweed extract also demonstrated to be efficient in the inhibition of fungal growth, namely, Aspergillus fumigatus , Aspergillus terreus, and Aspergillus flavus [ 220 ].…”
Section: Pharmacological Potential Of the Invasive Seaweedsmentioning
confidence: 99%
“…In fact, dichloromethane and hexane extracts from A. taxiformis , ethanol-hexane:ethylacetate and ethanol-ethylacetate fractions from A. taxiformis and A. armata also showed significant effect on L. donovani promastigotes with IC 50 values ranging from 10 to 20 μg/mL [ 52 ]. Additionally, ethanol extract of A. taxiformis was shown to be active against promastigotes and axenic amastigotes of L. infantum with IC 50 values of 25 μg/mL and 9 μg/mL, respectively and acceptable safety profile on VERO and DH82 cell lines (CC 50 > 90 μg/mL) [ 53 ]. These activities of Asparagopsis species could be attributed to the presence of volatile halogenated compounds (halomethanes, haloethers, haloacetals) which have been otherwise described as responsible for the antimicrobial properties of A. armata [ 67 ].…”
Section: Current Status Of Antileishmanial Drug Discovery From Marmentioning
confidence: 99%
“…In the last ten years (Table S1), research has focused on the potential of seaweed extracts in the pharmaceutical field as antimicrobics [154][155][156][157][158][159][160], anticoagulants [161,162] and antidiabetics [64]. In the technological field, biomaterial as bio-oils [163] was obtained from Gracilaria gracilis, whereas chlorophylls from Undaria pinnatifida were tested as dye in photovoltaic cells [164].…”
Section: Research Harvesting and Industrial Activity Of Seaweedsmentioning
confidence: 99%